Research Progress on Acupuncture Treatment for Lumbar Muscle Strain - Ren, Yidi; Su, Tongsheng (Journal of Contemporary Medical Practice, 2025)
Lumbar muscle strain is a common clinical condition, and acupuncture plays a significant role in its treatment. This article provides a comprehensive overview of recent advances in acupuncture therapy for lumbar muscle strain, aiming to clarify the current state of clinical application. By examining the therapeutic methods employed in acupuncture treatment and integrating theoretical knowledge from traditional Chinese medicine (TCM), the study conducts an in-depth analysis of the TCM-based management of lumbar muscle strain. The findings offer new perspectives and directions for future research on the efficacy and mechanisms of acupuncture therapy.